PENINGKATAN KUALITAS PRODUKSI DENGAN PENERAPAN DESAIN EKSPERIMEN SHAININ DI PT. XYZ - Audia Laila Maulita S.; Eric Wibisono; Mochammad Arbi Hadiyat (Perpustakaan Universitas Surabaya, 2018)
The high percentage of re jects due to de fects during the production process in P T. XYZ, encouraged the researcher to de sign experiments using Shainin method. Shainin method begins with multi-vary testing to see the spread of rejected products proportion based on time to time, unit to unit and within unitgroups. The tests performed showed significant gains in all three groups (A, C, and D groups in the 3rd shifts and capper 1, 2). Furthermore, concentration chart testing shows the location of defects that recur in group A and the group C on capper 1 and capper 2. Paired comparison testing results indicate torque band as Red X and seal torque as Pink X. Moreover, the results of product / process search shows pressure drying closing cone as Red X and low pressure lifting as Pink X. The four tests performed on these factors indicate interaction so that response surface can be performed. Thus, it was obtained that the value to minimize Green Y on low pressure lifting of parameter setting was 3.5-4.0 bar, closing cone of drying pressure was 2.1 to 3.0 bar, the torque band was 8.8 to 10, 9 Lb.in and seal torque was 6.0-7.5 Lb.in.